Medical Extended Reality Trials: Building Robust Comparators, Controls, and Sham - Susan Persky; Luana Colloca (JMIR Publications, 2023)
The explosive pace of development and research in medical extended reality (MXR) is a testament to its promise for health care and medicine. In comparison with this growth, there is a relative sparsity of rigorous clinical trials that establish the efficacy and effectiveness of these interventions. Explicating mechanisms of action across clinical areas and MXR applications is another major area of need. A primary impediment to these goals is a lack of frameworks for trial design, more specifically, the selection of appropriate controls that effectively address unique elements of MXR. This paper delineates a framework for designing controls, sham conditions, and comparators, as well as proposed considerations for MXR trial designs. Special consideration is given to the design of sham conditions. Improved designs would enable more robust findings and the development of generalizable knowledge that could be adopted across MXR interventions.